EFEKTIVITAS METODE PEMBELAJARAN PART AND WHOLE TERHADAP KETERAMPILAN GERAK SENAM LANTAI ROLL DEPAN SISWA KELAS X DI SMAN 1 BABELAN - Nur Anggraeni Tj; Dikdik Fauzi Dermawan; Rahmat Iqbal (Universitas Hamzanwadi, 2026)
This research was motivated by problems in learning floor gymnastics forward roll at SMAN 1 Babelan, where students had difficulty mastering movement techniques because the conventional method used by the teacher was only in the form of whole movement demonstrations without being broken down into simple parts, causing technical errors to recur. This study aimed to determine the effectiveness of the Part and Whole learning method on the forward roll floor gymnastics skills of tenth-grade students. The study employed a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The sample consisted of 84 students divided into experimental class (n=42) and control class (n=42). The instrument was a forward roll movement skills test. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, Levene's Test for homogeneity, Independent Sample t-Test, and N-Gain analysis. The results showed that the mean score of the experimental class increased from 60.29 to 72.83, while the control class increased from 60.69 to 64.07. The t-test result showed a significance value of 0.012 (p < 0.05), indicating a significant difference between the two classes. The N-Gain score of the experimental class was 0.316 (moderate category), higher than the control class which obtained 0.086 (low category). This study concludes that the Part and Whole learning method is proven more effective in improving students' forward roll floor gymnastics skills.